Molecular characterization of wood ear mushrooms (Auricularia sp) from Kakamega forest in western Kenya - Onyango, B.O.; Mbaluto, C.A.; Mutuku, C.S.; Otieno, D.O. (Mushroom Research Foundation, 2016)
Tanzania natural forests harbor several indigenous edible mushrooms that are meagerly exploited due to various reasons including unawareness on their potential values. This study establishes antioxidant potentials of seven wild edible mushroom species, and their two domesticated forms. The investigation used mushroom methanolic extract for antioxidant activities’ determination. A DPPH (1, 1-diphenyl-2-picrylhydrazyl) radical was used as a substrate to determine radical scavenging abilities whereas ferrozine was employed to determine ferrous ion chelating abilities. Additionally, quantitative analyses for β-carotene, lycopene, flavonoids, and total phenolic compounds were done using spectrophotometric assay. Mushrooms analysed displayed amazing antioxidant potentials which varied between different species and between the wild and domesticated forms of the same species. The range of EC50 values for DPPH free radical scavenging activity (DRSA) was 0.075 ̶ >0.3 mg/mL, with the strongest and weakest EC50 recorded from P. tenuiculus and the wild Amylosporus sp. IJ-2014, respectively. The range of EC50 values for ferrous ion chelating activity (FICA) was <0.1 ̶ 0.455 mg/mL, with the strongest and weakest EC50 noted in domesticated Amylosporus sp. IJ-2014 and L. sajor-caju, correspondingly. The maximum and minimum total phenolic content (TPC) recorded were 537.39 and 160.97 mg GAE/100g, from domesticated Amylosporus sp. IJ-2014 and Laetiporus sp. IJ-2014, respectively. The highest and least quantities of β-carotene (BC) recorded were 48.59 and 5.56 mg/100g, from P. tenuiculus/wild Amylosporus sp. IJ-2014 and P. cystidiosus, respectively. Lycopene contents (LC) ranged from 2.24 to 18.95 mg/100g, with P. cystidiosus and P. tenuiculus having the slightest and peak values, correspondingly. Maximum value for total flavonoid contents (TFl) recorded was 25.27 mg QE/100g from P. tenuiculus whereas the minimum value was 3.71 mg QE/100g from P. cystidiosus. Due to the antioxidant potentials of these mushrooms, people are advised to maximally exploit them for improved nutrition and health.